2019
DOI: 10.1007/s12020-019-02086-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antiproliferative effect of lanreotide autogel in advanced gastroenteropancreatic neuroendocrine neoplasms

Abstract: Purpose The antiproliferative properties of lanreotide autogel (LAN) in gastroenteropancreatic neuroendocrine neoplasms (GEP NENs) were demonstrated in the CLARINET study. However, there is limited literature regarding factors that affect progression-free survival (PFS) in patients with GEP NENs treated with LAN. Methods We identified a total of 191 treatment-naive patients with advanced GEP NENs and positive SSTR uptake on imaging (Octreoscan or 68 Gallium DOTATATE Positron Emission Tomography [ 68 GaPET]) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The antiproliferative and pro-apoptotic activities of somatostatin analogues (SSAs) are mainly used in the treatment of highly differentiated GEP-NENs and other tumors that express SSTRs [ 22 , 46 , 183 , 254 , 255 , 256 , 257 ]. However, treatment in SSTR-negative NETs are also presented [ 254 ].…”
Section: Somatostatin—implications For Cancer Therapymentioning
confidence: 99%
“…The antiproliferative and pro-apoptotic activities of somatostatin analogues (SSAs) are mainly used in the treatment of highly differentiated GEP-NENs and other tumors that express SSTRs [ 22 , 46 , 183 , 254 , 255 , 256 , 257 ]. However, treatment in SSTR-negative NETs are also presented [ 254 ].…”
Section: Somatostatin—implications For Cancer Therapymentioning
confidence: 99%
“…An increased tumor grade [ 42 , 172 , 179 , 223 ], presence of a poorly-differentiated tumor [ 175 ] and an increasing Ki-67 index [ 173 ] are reported to correlate with worse outcomes with SSA treatment ( Table 2 , Right Panel). Some studies reported that a Ki-67 threshold of 5% was more predictive of PFS with SSA treatment than the cut-off value proposed by 2010 WHO classification to separate G1 and G2 (i.e., <3%) [ 172 , 224 ].…”
Section: Predictive Factors For Response To Ssa In Advanced Pannensmentioning
confidence: 99%
“…Some studies reported that a Ki-67 threshold of 5% was more predictive of PFS with SSA treatment than the cut-off value proposed by 2010 WHO classification to separate G1 and G2 (i.e., <3%) [ 172 , 224 ]. SSA therapy is less effective in patients with bone and peritoneal metastases [ 173 ], as well as with any liver metastases [ 42 ] or a high hepatic tumor load [ 173 , 174 , 177 , 179 , 225 ], suggesting its limited role in advanced panNEN patients with aggressive tumors.…”
Section: Predictive Factors For Response To Ssa In Advanced Pannensmentioning
confidence: 99%
See 2 more Smart Citations